Analysis of the Effect of Fabrication Failure Factors and Operational Failure Factors on Equipment Reliability Mediated by Maintenance Technology 4.0 with the Use of SEM (Structural Equation Modelling) Methods (Case Study of Genset Products at PT. XYZ) - SIMAN, Siman; RAJAGUKGUK, Jenni Ria; SUWANDA, Suwanda (International Journal of Environmental, Sustainability, and Social Science, 2024)
This study aims to analyze the effect of fabrication and operational failure factors on equipment reliability. In addition, this study also examines the impact of fabrication and operational failure factors on Maintenance Technology 4.0 and the impact of Maintenance Technology 4.0 on equipment reliability. This quantitative research was conducted at the genset product of PT XYZ. The sample of this research is the technicians of PT XYZ spread in branches throughout Indonesia, who have run Maintenance Technology 4.0 in the repair and maintenance of gensets. A non-probability sampling method, namely convenience sampling, was used to get the sample used. The number of respondents was 102 technicians. The analytical tool used is SEM-PLS 4.0. The results prove that the fabrication and operational failure factors do not affect the equipment's reliability. In contrast, the fabrication failure factor does not affect Maintenance Technology 4.0 but differs from the operational failure factor, which influences Maintenance Technology 4.0. Next, Maintenance Technology 4.0 affects equipment reliability. Meanwhile, Maintenance Technology 4.0 mediates the effect of operational failure factors on equipment reliability. In addition, Maintenance Technology 4.0 does not mediate the impact of fabrication failure factors on equipment reliability.